ANALISIS RANTAI PASOK TOMAT DI KECAMATAN SUKAU KABUPATEN LAMPUNG BARAT - Paramita, Yulita Siska; Hasyim, Ali Ibrahim; Affandi, Muhammad Irfan (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to find outsupply chain, flow patterns of goods, information, and finance, supply chain performance, and marketing efficiency. The research was carried out in two villages namely Tanjung Raya Village and Hanakau Village of Sukau District. Determination of the location of the study was conducted purposively considering the area as a center for vegetable production in West Lampung Regency. The respondents involved were 74 people, consisting of 30 vegetable farmers, 10 agents, 12 wholesalers, and 22 retailers. The first and second objectives were analyzed using a descriptive method, the third objective was analyzed using supply chain performance measurement, and the fourth objective was analyzed using marketing efficiency. The results proved that stakeholders involved in the tomato supply chain consist of farmers, agents, wholesalers, retailers, and consumers. The flow of goods occured from upstream to downstream, and the flow of information occurs from upstream to downstream. Meanwhile, financial flow occured from downstream to upstream. The tomato supply chain performance was in a good criteria, because it reaches the foodscor card value, but the distribution is inefficient because the overall ratio of profit margins among marketing institutions is spread unevenly and less than zero. Key words: marketing efficiency, performance, supply chain, tomato